Respuesta :

Answer:

M-1 L3 T-2

Explanation:

Where,

M = Mass

L = Length

T = Time

Derivation

From Newton’s law of gravitation,

Force (F) = [GM1M2] × r-2

Gravitational Constant (G) = F × r2 × [Mm]-1  . . . . (1)

Since, Force (F) = Mass × Acceleration = M × [LT-2]

∴ The dimensional formula of force = M1 L1 T-2 . . . . (2)

On substituting equation (2) in equation (1) we get,

Gravitational Constant (G) = F × r2 × [Mm]-1

Or, G = [M1 L1 T-2] × [L]2 × [M]-2 = [M-1 L3 T-2].

Therefore, the gravitational constant is dimensionally represented as M-1 L3 T-2.